Komunikasi Keluarga dan Resiliensi pada Perempuan Korban Kekerasan Berbasis Gender Online - Sri Mustika; Tellys Corliana (Institut Pertanian Bogor, 2022)
The virtual world is not a safe place for women. Many women are victims of online gender-based violence (KBGO). This study aims to examine family communication, resilience, and KBGO victims. Researchers used a qualitative approach with a descriptive type. Participants in this study amounted to five people. These five informants were chosen purposively. Data was collected by observation, in-depth interviews, and literature study. Data analysis was carried out using the Miles and Huberman model. This research was conducted in Jakarta and its surroundings from February to August 2021. Researchers found that the victims of KBGO were women who were active on social media, including Twitter, Facebook, and Instagram. Not all victims of violence know the perpetrators, although some recognized the perpetrators as close people, such as friends from a community and siri's ex-husband. Not all victims have the courage to share their problems with their families. The pattern of family communication also determines the victim's openness to her family. Likewise, the resilience of the victim in dealing with this case is closely related to the communication pattern of her family. Victims who have consensual communication patterns have resilience and managed to get through the case well. However, the support of friends can help the victim in overcoming the problem.